Baicalin attenuates monocrotaline-induced pulmonary hypertension through bone morphogenetic protein signaling pathway - Zhang, Zhaohua (Oncotarget, 2017)
Baicalin, a flavonoid compound extracted from roots of Scutellaria baicalensis Georgi (huang qin), it has been shown to effectively attenuates pulmonary hypertension (PH), however, the potential mechanism remains unexplored. In this study, we investigated the potential mechanism of baicalin on monocrotaline (MCT)-induced PH in rats. The results showed that baicalin attenuated lung damage in PH rat model through inhibiting the pulmonary arterial smooth muscle cell proliferation and induction of cells apoptosis. Furthermore, we demonstrated that baicalin inhibition the expression of nuclear factor-κB (NF-κB) p65 and bone morphogenetic protein (BMP) antagonists gremlin-1, but increased the expression of inhibitor of NF-κB (I-κBα), BMPR2, BMP-4, BMP-9 and Smad1/5/8. Additionally, baicalin suppression endothelial-to-mesenchymal transition in PH lung tissue. Collectively, we confirmed that baicalin via inhibition of NF-κB signaling to further activation of BMP signaling to have a therapeutic effect on PH and providing a promising therapeutic strategy for PH.